Measurement of ski deflection and ski-snow contacting pressure in an actual ski turn on the snow surface - Tatsuno, D.; Yoneyama, T.; Kagawa, H.; Scott, N.; Osada, K. (Science and Skiing IV, 2008)
INTRODUCTION: The authors have developed the measuring system which detects both ski deflection and ski-snow contacting pressure during the actual turn on the snow surface. The detail is described in another paper in this Conference. In this study, measured result on a long turn is shown and the relation between the ski deflection and the ski-snow pressure is investigated.